Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Baju Thrift Di Jeanette Thrift Store Maumere - Maria Anggelina Bissi; Dekrita, Yosefina Andia; Dimas Realino (Jurnal Projemen UNIPA, 2026)
The background of this study is the instability of consumers' purchasing decisions for thrift clothing at Jeanette Thrift Store Maumere, which is influenced by price and product quality. This study aims to (1) describe the price, product quality, and consumers' purchasing decisions for thrift clothing at Jeanette Thrift Store Maumere; (2) examine the effect of price on consumers' purchasing decisions; (3) analyze the effect of product quality on consumers' purchasing decisions; and (4) determine the simultaneous effect of price and product quality on consumers' purchasing decisions at Jeanette Thrift Store Maumere. The population of this study consisted of all consumers who purchased thrift clothing at Jeanette Thrift Store Maumere. This research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to the respondents. The data were analyzed using descriptive statistics and inferential statistics, namely multiple linear regression analysis. Hypothesis testing was conducted using the t-test and F-test. The results of the descriptive statistical analysis indicate that respondents' perceptions of price, product quality, and purchasing decisions are categorized as good. The inferential statistical analysis shows that price has a positive and significant effect on consumers' purchasing decisions for thrift clothing at Jeanette Thrift Store Maumere. Product quality also has a positive and significant effect on consumers' purchasing decisions. Furthermore, price and product quality simultaneously have a significant effect on consumers' purchasing decisions. These findings indicate that the more affordable and appropriate the price offered and the better the product quality provided, the higher the consumers' purchasing decisions.